Sinus surgery postpones chronic Gram-negative lung infection: cohort study of 106 patients with cystic fibrosis - Alanin, Mikkel Christian; Aanaes, Kasper; Hoiby, Niels; Pressler, Tania; Skov, Marianne; Nielsen, Kim G.; Taylor-Robinson, David; Waldmann, Elisabeth; Johansen, Helle Krogh; Von Buchwald, Christian (Rhinology, 2016)
In patients with cystic fibrosis (CF) the sinuses are a bacterial reservoir for Gram-negative bacteria (GNB). From the sinuses the GNB can repeatedly migrate to the lungs. In a one-year follow-up study, endoscopic sinus surgery (ESS) with adjuvant therapy reduced the frequency of pulmonary samples positive for GNB. We investigated whether the effect is sustained.We report the effect of ESS and adjuvant therapy three years postoperatively in a CF cohort participating in this prospective clinical follow-up study. The primary endpoint was the lung infection status defined by Leeds criteria.One hundred and six CF patients underwent ESS; 27 had improved lung infection status after three years. The prevalence of patients free of lung colonization with GNB significantly increased from 16/106 patients (15%) preoperatively to 35/106 patients (33%) after three years. The total cohort had decreasing lung function during follow-up; however, in 27 patients with improved lung infection status lung function was stable. Revision surgery was performed in 31 patients (28%).ESS with adjuvant therapy significantly improves the lung infection status for at least three years in our cohort of patients with CF and may postpone chronic lung infection with GNB and thus stabilize lung function.
EVALuna2:5565